Inequities in Urban Health: A Synthesis of Evidence - Jaya, Sreejini (International Journal of Social Sciences and Management, 2019)
Cities throughout the world, no matter from developed or developing countries, had acted as foci of attraction for people from resource-poor settings. The co-existence of advantages and disadvantages of city life creating urban disparities is an interesting phenomenon. The research questions driving this synthesis are based on health inequities in urban areas in low and middle income countries (LMICs) with a special focus on India, on the extent of urban health inequities, the dimensions of urban health inequities and the factors associated with, or pathways and mechanisms driving urban health inequities. Based on an assessment of each article as to whether it describes a health gap, seeks to identify correlates or determinants of the gaps or to unravel pathways and mechanisms contributing to urban health inequities, we have come up with a framework of inter-connected factors contributing to urban health inequities. We found that undeniably urban health inequity was directed and shaped by urban governance, inequitable urban living environment which includes the physical and social environment, urban service delivery component of the health system and other public service delivery systems and ultimately how the above-said factors have an effect on the urban poor beneficiary in creating such health inequities. This proposed network of inter-connected linkages in urban health inequities provides a detailed knowledge of the various factors influencing urban health inequities and how these operate in generating the inequity share. Int. J. Soc. Sc. Manage. Vol. 6, Issue-3: 54-62